Working Time Accounts and Turnover - Andrey Launov (Center for Economic Studies and ifo Institute (CESifo), 2019)
Working time account is an organization tool that allows firms to smooth their demand for hours employed. Descriptive literature suggests that working time accounts are likely to reduce layoffs and inhibit increases in unemployment during recessions. In a model of optimal labour demand I show that working time account does not necessarily guarantee less layoffs at the firm level. These may be reduced or increased depending on whether the firm meets economic downturn with surplus or deficit of hours and on how productive the firm is. In expected terms, however, working time account reduces net job destruction at almost any level of firm's productivity. Model predictions are consistent with dynamics of aggregate turnover in Germany during the Great Recession.
Keywords: J23; J63; 330; labour demand; working hours; working time account; turnover; layoff; Great Recession; Germany